Late Oligocene to early Miocene humidity change recorded in terrestrial sequences in the Ili Basin (south-eastern Kazakhstan, Central Asia) - Hellwig, Alexandra; Voigt, Silke; Pross, Jörg; Gerdes, Axel (Sedimentology, 2018)
Enhanced aridification of Central Asia driven by the combined effects of orogenic surface uplift, Paratethys retreat, changes in atmospheric moisture transport and global cooling is one of the most prominent Cenozoic climate change events of the Northern Hemisphere. Deciphering regional long-term patterns of Central Asian hydrology is, therefore, a key element in understanding the role of Northern Hemisphere mid-latitude drying in the global hydrological system. This study characterizes long-term palaeoenvironmental conditions between the late Oligocene and early Miocene in south-eastern Kazakhstan based on stable isotopes, elemental geochemistry and laser ablation uranium-lead geochronology from alluvial, fluvial and pedogenic deposits. Sedimentary facies and geochemical weathering indices suggest an increased surface and groundwater discharge fed by orographically enhanced precipitation in the Tien Shan hinterland. In contrast, pedogenic stable isotope data and elevated rates of magnesium fixation in clay minerals mirror enhanced rates of evaporation in the vadose zone due to protracted aridification. This study posits that pronounced surface uplift of the Tien Shan Mountains during the Oligocene-Miocene transition promoted regionally increased orographic precipitation and the development of fluvial discharge systems.
Gesehen am 14.02.2018